2010
DOI: 10.1021/bi100502z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Structural Characterization of a Heterohexamer 4-Oxalocrotonate Tautomerase from Chloroflexus aurantiacus J-10-fl: Implications for Functional and Structural Diversity in the Tautomerase Superfamily,

Abstract: Abstract4-Oxalocrotonate tautomerase (4-OT) isozymes play prominent roles in the bacterial utilization of aromatic hydrocarbons as sole carbon sources. These enzymes catalyze the conversion of 2-hydroxy-2,4-hexadienedioate (or 2-hydroxymuconate) to 2-oxo-3-hexenedioate, where Pro-1 functions as a general base and shuttles a proton from the 2-hydroxyl group of substrate to the C-5 position of product. 4-OT, a homohexamer from Pseudomonas putida mt-2, is the most extensively studied 4-OT isozyme and the founding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(107 citation statements)
references
References 38 publications
(133 reference statements)
4
103
0
Order By: Relevance
“…The kinetic parameters are comparable to those obtained for 4-OT and greater than those obtained for cis -CaaD with a 400-fold greater k cat , 2-fold greater K m , and 194-fold greater k cat / K m . 36,37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic parameters are comparable to those obtained for 4-OT and greater than those obtained for cis -CaaD with a 400-fold greater k cat , 2-fold greater K m , and 194-fold greater k cat / K m . 36,37 …”
Section: Resultsmentioning
confidence: 99%
“… a The kinetic parameters were measured using the assay described in the text in 20 mM Na 2 HPO 4 buffer (pH 9) at 22 °C. b The kinetic parameters are from reference 36. c The kinetic parameters are from reference 37. …”
Section: Figurementioning
confidence: 99%
“…In the course of ongoing database searches for new TSF members, a heterohexamer 4-OT (hh4-OT) was identified and characterized by mechanistic and structural studies [36]. Sequence analysis identified two “tautomerases” in the thermophile Chloroflexus aurantiacus J-10-fl.…”
Section: Characterization Of Catabolic and Biosynthetic 4-ot Family Mmentioning
confidence: 99%
“…The puzzle was solved when co-expression of the two genes produced a stable heterohexamer (verified by the crystal structure) where each dimer consists of an α and β-subunit [36]. Kinetic, mutagenesis, and crystallographic studies identified βPro-1, αArg-12, and αArg-40 as critical residues, and indicated that the hh4-OT has comparable kinetic parameters to those of 4-OT (using 1 ) and an analogous mechanism [36]. The change in oligomeric structure (homohexamer vs heterohexamer) does not appear to affect catalysis, but might be related to thermostability.…”
Section: Characterization Of Catabolic and Biosynthetic 4-ot Family Mmentioning
confidence: 99%
See 1 more Smart Citation